الأساطير و الخرافات في رحلتي ابن فضلان و سلام الترجمان - أمین, نەبەز مجید (Sulaimani Journal for Humanities, 2025)
Leggends and Superstition in Ibn Fadlan and Salam Al-Targumans, trips The writings of the travelers played a great role in presenting an image about athers and impressing a number of general impressions and thoughts about other peoples , whether these impressions were or wrong. Studying these legends and sperstitious storries in the ancient travelers in the Middle Ages is in need of an independent and detailed study, this study does not restrict on collecting texts and making investigations only, but it must extract the religious structure also that these stories and legends depended on, and what Islamic thought expresses in its way of looking at the relation between man and universe. These stories and legends shed light indirectly and symbolically on the condition of the Islamic society during that period, especially the prevailing way of thinking in the society , moreover these stories and represent a significant part of the popular legacy of humanitarian culture generally. These legends and superstitions in the modern anthographical thought include a certain imagination about a certain event or a person who had a historical existence, and emphasis a certain value of their symbols which represent that event or person within the frame work of exaggeration I divided this research in two parts: The first part deals with Ibn Faslans trip , its impules , aims and contents, and what he wrote in his famous letter what he had seen about Bulgarians , Al-Kazar and Russains ,I also deait with the legends and superstitions in this trip, then evaluating this trip from different aspects , historical geagraphical and social . The second part includes Salam Al-Targumans' trip , in which I clarified the contents and aims of Al-Targumans trip to Yagug and Magugs dam, the places he passed by during his trip and what he had seen. Moreover I dealt with the legends and superstitions in this trip and the specialists point of view about them. I used different sources in writing this research like Mugam Al-buldan by Yaqut Al-Hamawi who transferred most of what he had seen and both of Ibn fadlan and salam Al-Targuman had written it down, I also used (History of Geographical Literature)) by Kratchkofisy for discovering some of the important aspets in this research, like mentipning the opinions of the specialists about these two trips. As far as other mentioned sources are concerned I also made use of them.